Bites caused by Giant Water Bugs belonging to belostomatidae family (Hemiptera, Heteroptera) in humans: A Report of Seven cases - Haddad Júnior, Vidal [UNESP]; Schwartz, Elisabeth F.; Schwartz, Carlos Alberto; Carvalho, Lucélia Nobre (SAGE Publications, 2010)
We report 7 cases of patients bitten by giant water bugs, large predatory insects belonging to the Belostomatidae family (Hemiptera, Heteroptera). These insects have toxic saliva capable of provoking intense pain and paralysis in vertebrates. Victims experienced intense, excruciating pain and 1 manifested hypoesthesia in the forearm. Bites by Belostomatidae are often reported by clinicians working in areas where these insects live, but there are no detailed case reports in the medical literature. There are no specific treatment modalities known to be effective, making prevention an important strategy. © 2010 Wilderness Medical Society.
Keywords: Belostoma; Belostomatidae; Bites; Giant water bugs; Hemiptera; Human injuries; Lethocerus